Tolerance of the association sucralfate / Cu-Zn salts in radiation dermatitis - De Rauglaudre, G; Courdi, A; Delaby-Chagrin, F; d'Hombres, A; Hannoun-Levi, J-M; Moureau-Zabotto, L; Richard-Tallet, A; Rouah, Y; Salem, N; Thomas, O; Nocera, T; Mery, S; et al. (Annales de dermatologie et de vénéréologie, 2008)
The aim of this study was to evaluate the tolerance of topical application of the combination sucralfate / copper zinc salts in radiation dermatitis in women suffering from breast cancer and treated by radiotherapy. 47 patients (average age : 57,5 years) that have to be treated by radiation therapy on non lesional areas, were included into this open multicentric study. They had to apply Cicalfate cream twice a day, from the fi rst radiation therapy session and during 10 weeks. Patients were treated by photon- or electrontherapy (72 % et 28 %, respectively; cumulated total dose : 58,6Gy). Tolerance was considered to be excellent. The radiation dermatitis (score NCIC > or = 2) was noted at the 3rd week of radiotherapy only in 5 % of the subjects and in 53 % of the subjects, the last week of treatment. Pruritus was significantly increased at D21. Pain and discomfort were increased at D28, but remained low intensity. The soothing effect of the combination of sucralfate/ copper zinc salts were considered satisfying or very satisfying by investigators and patients during the study, varying from 94 to 100 % of satisfaction. The impact of radiation therapy on the patients'quality of life, assessed by DLQI, evaluated at the end of the study was not statistically different from the score calculated at D7 (DLQI=0,8 et D7 versus DLQI=1 at D70). Thus, topical application of the combination sucralfate / copper zinc salts can be used in the indication radiation dermatitis.